2011
DOI: 10.3892/ijmm.2011.692
|View full text |Cite
|
Sign up to set email alerts
|

hSav1 interacts with HAX1 and attenuates its anti-apoptotic effects in MCF-7 breast cancer cells

Abstract: Abstract. It has been reported that Salvador (SAV) is a core component of the Salvador-Warts-Hippo (SWH) pathway that restricts cell number, by functioning as a dual regulator of cell proliferation and apoptosis in Drosophila. However, the function of its human ortholog hSav1 (also called hWW45) in mammalian cells is poorly understood. In this study, we identified hematopoietic cell-specific protein 1 (HS1)-associated protein X-1 (HAX1), a 35-kda protein localized to cell mitochondria, as a novel binding partn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…Oncomine Cancer Microarray database [25] (http://www.oncomine.org) were used to study gene expression of Six1 in human pancreatic cancer samples as we previously described [26]. Gene expression data were also obtained from NCBI Gene Expression Omnibus (GEO) database (accession numbers GSE15471, GSE32676 and GSE28735; http://www.ncbi.nlm.nih.gov/geo) [27][29].…”
Section: Methodsmentioning
confidence: 99%
“…Oncomine Cancer Microarray database [25] (http://www.oncomine.org) were used to study gene expression of Six1 in human pancreatic cancer samples as we previously described [26]. Gene expression data were also obtained from NCBI Gene Expression Omnibus (GEO) database (accession numbers GSE15471, GSE32676 and GSE28735; http://www.ncbi.nlm.nih.gov/geo) [27][29].…”
Section: Methodsmentioning
confidence: 99%
“…Western blot analyses were performed as previously described (21). For immunoblotting of LC3 in SH-SY5Y cells, mycoplasma-infected (infected at the MOI ratio of 10:1 for 24 h) cells and control SH-SY5Y cells were serum starved for 2 h prior to treatment with 0.1% dimethylsulfoxide (DMSO) or Bafilomycin A1 (Baf A1; 10 nM) for 4 h; and lysates were collected for western blot analysis against LC3.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study, yeast two-hybrid screening demonstrated that HAX-1 had a key role in the Salvador-warts-hippo signaling pathway, which is an important supplement for the classic apoptosis pathway ( 16 , 17 ). The present study aimed to analyze the potential prognostic significance of HAX-1 in CRC by detecting its expression levels in human colorectal tumor tissues, and to assess the role of HAX-1 in apoptosis and proliferation using gene-overexpression and silencing methods.…”
Section: Introductionmentioning
confidence: 99%